1994
DOI: 10.1002/joc.3370140405
|View full text |Cite
|
Sign up to set email alerts
|

Estimating continental and terrestrial precipitation averages from rain‐gauge networks

Abstract: Influences of varying rain‐gauge networks on continental and terrestrial precipitation averages (derived from data observed on those networks) are evaluated. Unsystematically and systematically designed station networks are considered, the latter being represented by the NCAR World Monthly Surface Station Climatology, which contains hand‐picked but time‐varying networks that date back to the 1800s. Biases arising from spatially uneven and temporally variable precipitation‐observing networks can be significant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…Lvovich [29] estimates that a global mean of 24% of P travels to streams by overland flow, leaving only 11% of P for deep infiltration. The mean terrestrial P is reported as between 850 mm and 1100 mm [30], with a mean of 975 mm. Sixty-four percent of 975 mm is 624 mm, leaving 351 mm for P − AET.…”
Section: Predicting a Typical Soil Depthmentioning
confidence: 99%
“…Lvovich [29] estimates that a global mean of 24% of P travels to streams by overland flow, leaving only 11% of P for deep infiltration. The mean terrestrial P is reported as between 850 mm and 1100 mm [30], with a mean of 975 mm. Sixty-four percent of 975 mm is 624 mm, leaving 351 mm for P − AET.…”
Section: Predicting a Typical Soil Depthmentioning
confidence: 99%
“…Willmott et al (1994) estimate that, for the region's gauge density (less than 20 stations per 10 6 km2), estimates of precipitation can be in error by as much as 100 to 700 mm/yr.…”
Section: Introductionmentioning
confidence: 94%
“…This can be caused by measurement errors, incompleteness of the historical records and topographic influences or, more frequently, by the low density of measuring locations inside the basin; see e.g. Hutchinson (1970), Willmott et al (1994), Gebremichael and Krajewski (2004), Langousis (2005), Veneziano and Langousis (2005a) and Veneziano et al (2006). The latter is an important issue for many catchments in Greece, and other countries in the Mediterranean region, which causes important problems in the calculation of annual water budgets and the calibration of hydrological models.…”
Section: Introductionmentioning
confidence: 99%